HIF-1α regulates tumor progression in a human epithelial ovarian cancer model - España de Marco, Maria Jose (2021)
Ovarian cancer is the seventh most common cancer in women and the eighth cause of cancer death. The treatment of this disease has been the same for the past decades, and the development of new drugs is needed. Hypoxia is a common characteristic of solid tumors, usually associated with a more aggressive phenotype. The main transcriptional factor involved in this process is Hypoxia Inducible Factor 1 alpha (HIF-1α).